Juridical Review Division of Inheritance to Heirs of Different Religions Through a Mandatory Will (Supreme Court Decision Number 218 K/Ag/2016) - Novita Kusumawati; Farahdinny Siswajanthy; Mahipal; Yenny Febrianty (Periodica Journal, 2023)
It is a fact of life that humans are not alone. Humans are predestined to always live together for the sake of their lives, giving rise to a type of law whose provisions govern that life and is called "Civil Law".private right). The law of inheritance is very closely related to the scope of human life, because every human being will experience a legal event called death. Further legal consequences arise, with the occurrence of the legal event of a person's death, including the problem of how to manage and continue the rights and obligations of someone who has died. Settlement of rights and obligations as a result of a person's death, is regulated by inheritance law. The nature of the research used in this writing is analytical descriptive, while the type of research used in writing this law is normative research. The data collection technique used by the author in this thesis is Library Research (Library Researh) Data processing is done qualitatively.
Keywords: obligatory will; different religions